Problematika Implementasi Eksekusi Harta Pailit Oleh Kreditur Separatis Dan Kurator Perspektif Keadilan - Saija, Ronald (KANJOLI Business Law Review, 2024)
When executing bankruptcy assets begins, it is important to remember that separatist creditors as holders of material guarantees have a special position to execute themselves on bankrupt assets which are the object of their material guarantees. In a bankruptcy case, there are actually 2 (two) parties who can apply for execution, namely the Curator and the separatist creditor. This is the problematic implementation of bankruptcy law in Indonesia regarding bankruptcy assets belonging to bankruptcy debtors. As for the problem being studied is: "how is the legal analysis related to the implementation of the execution of debtor bankruptcy assets by Separatist Creditors and Curators from a justice perspective?". The aim of this research is to find solutions to problems objectively. The research method used is normative juridical research which is descriptive-qualitative in nature, by examining legal materials, both primary legal materials and secondary legal materials through related literature studies. The analysis used in this research is qualitative analysis to answer the problems studiedred.